Do assessment loads affect student success? An investigation at an Economics Department at the undergraduate level - Yu, D.; Swanepoel, C.; Sims, D.; Anciano, F. (South African Journal of Higher Education, 2023)
Assessments plays an important role in Higher Education as a cornerstone and driver of learning and teaching activities, curriculum development and renewal, achievement of learning objectives and student academic success, as well as the development of graduate attributes. Assessment load, however, in terms of over-assessment (along with under-assessment), is a blurred concept that is difficult to define qualitatively and measure quantitatively. To address this gap in research, based on a comprehensive literature review, we developed a multidimensional assessment index (MAI), with eight indicators, to measure over-assessment. These indicators include features of continuous assessment (total number, mark allocation or size, weighting, degree of difficulty, frequency and scheduling, type, content coverage and repetition) and the presence, or absence, of a single high-stakes final examination. We applied these indicators to a case study of an undergraduate Economics, consisting of 12 modules across 3 years of study, at a university in South Africa. The MAI was then compared with the pass rate, as a measure of student success, and there was a moderate and negative correlation between the MAI (high assessment loads) and pass rate variables. Lastly, the indicator with the strongest correlation with pass rate was the length of assessments (or proportion of continuous assessments with a high mark count). It is hoped that this study helps fill the gaps in existing literature on definition and measurement of assessment loads, and the practical use of the MAI as a tool to evaluate assessment load and inform the design of assessment for student learning and success.